Hydrodynamics of Palu Bay during the Event of 2018 Palu Earthquake and Tsunami - Semeidi Husrin; Fatimah Yasmin Azahra; Joko Prihantono; Armyanda Tussadiah; Rizal Abida (Marine Geological Institute of Indonesia, 2020)
The devastation of coastal area in Palu Bay few minutes after the September 28th, 2018 Sulawesi earthquake showed high variation of tsunami arrival time as well as the tsunami run-up and inundation. Recent findings showed that both local submarine landslides and the normal-slip components inside the Palu Bay may contribute to the generation of tsunami. However, the fact that the event occurred during high tide, the hydrodynamic characteristics of this narrow bay and their role in the dynamics of the generated of tsunami were unknown. Hydrodynamics simulation (Mike21-flow model) using the latest available bathymetry field data (the 2018 deep water of the Indonesian navy data and 2015 shallow water of the BIG data) was conducted to investigate the variation of sea levels and tidal currents within the bay during the event of earthquake and tsunami or within the first 8 minutes timeframe. Results showed that significant increase of water elevation up to 6 cm and current velocity up to 1 cm/s directed towards the city of Palu were observed that may contribute to the dynamics of the tsunami e.g. the speed of tsunami arrival time and the transformation of tsunami. Therefore, considering that multiple tsunami arrivals were in few minutes after the earthquakes, the hydrodynamics of Palu Bay during the event should also be considered in future tsunami simulation scenarios.Keywords: Palu, Tsunami, Earthquake, Tides, Hydrodynamic Kerusakan kawasan pesisir di Teluk Palu beberapa menit setelah gempa bumi 28 September 2018 menunjukkan variasi yang sangat beragam pada tinggi tsunami, limpasan, waktu tiba dan jarak rendaman. Penemuan terkini memperlihatkan bahwa longsoran bawah laut dan meknisme patahan normal kemungkinan besar berkontribusi pada terjadinya tsunami. Namun, fakta bahwa kejadian tsunami terjadi saat kondisi pasang tinggi, karakteristik hidrodinamika dari teluk yang sempit ini dan perannya dalam tsunami yang terjadi belum diketahui. Simulasi hidrodinamika (Mike 21 – flow model) berdasarkan data batimetri terkini (Dinas hidroosenografi TNI AL dan BIG) menginvestigasi variasi muka air dan arus pasang surut saat kejadian gempa bumi dan tsunami atau dalam kurun waktu 8 menit setelah gempa utama. Hasil simulasi memperlihatkan peningkatan tinggi muka air yang cukup signifikan hingga 6 cm dan kecepatan arus hingga 1 cm/s menuju kota Palu yang dapat berkontribusi pada dinamika tsunami di Teluk Palu (waktu tiba dan transformasi tsunami). Oleh karena itu, dengan mempertimbangkan kedatangan tsunami yang terjadi dalam beberapa menit, hidrodinamika Teluk Palu perlu dipertimbangkan dalam skenario pemodelan tsunami di masa yang akan datang.Kata kunci: Palu, Tsunami, Gempa bumi, Pasut, Hidrodinamika